2022
DOI: 10.1007/s13384-022-00517-4
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive, colour-blind, and deficit: Understanding teachers' contradictory views of Aboriginal students’ participation in education

Abstract: This paper contributes evidence-based scholarship to how teachers understand the value of Aboriginal student-focussed programmes and how discourses of Indigeneity appear to influence those views. Interviews with n = 22 teachers across n = 3 secondary school sites in New South Wales highlighted teachers’ understanding of Aboriginal programmes as primarily contributing to students’ behavioural and academic improvement. The interviewed teachers spoke positively about Aboriginal students’ current academic achievem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Indigenous families and communities, in particular, have been unjustly labeled as "deficient, deviant, or uncaring" when they have refused to serve as "compliance officers for schools enacting settler-colonial agendas" (Bang et al, 2018, p. 5). International scholarship has found that deficit views and assimilative stances toward Indigenous students and their families by educational system leaders and teachers have proved similar in several settler colonial countries, including toward First Nations families in Canada (Madden et al, 2013;Milne, 2016;Washington, 2021b), Aboriginal communities in Australia (Fleer, 2004;Mander, 2015;Fricker et al, 2023;Weuffen et al, 2023), and Māori whānau in Aotearoa New Zealand (Mutch and Collins, 2012;Hindle et al, 2017;Jacobs et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Indigenous families and communities, in particular, have been unjustly labeled as "deficient, deviant, or uncaring" when they have refused to serve as "compliance officers for schools enacting settler-colonial agendas" (Bang et al, 2018, p. 5). International scholarship has found that deficit views and assimilative stances toward Indigenous students and their families by educational system leaders and teachers have proved similar in several settler colonial countries, including toward First Nations families in Canada (Madden et al, 2013;Milne, 2016;Washington, 2021b), Aboriginal communities in Australia (Fleer, 2004;Mander, 2015;Fricker et al, 2023;Weuffen et al, 2023), and Māori whānau in Aotearoa New Zealand (Mutch and Collins, 2012;Hindle et al, 2017;Jacobs et al, 2021).…”
Section: Introductionmentioning
confidence: 99%